Al-Si Alloys Casts by Die Casting A Case Study - Ružbarský, Juraj; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a study on the influence of selected technological parameters of die casting upon strength and use properties of Al-Si alloy casts produced in die casting. It contains a theoretical part describing the principles of casting technology, and its practical part revolves around the relationship between selected technological parameters of die casting in regard to strength and use properties represented by tensile strength and porosity of die casts. .
Current State of the Art -- Analysis of the Production Process -- Characteristics of the Cast -- Characteristics of Technological Parameters -- Cast Testing -- Characteristics of a Production Process -- Characteristics of the Cast -- Technological Parameters of Die Casting -- Assessment of Tensile Strength Rm -- Assessment of Cast Porosity -- Perspectives -- Conclusion.
Keywords: Metals; Machinery; Materials -- Analysis; Metals and Alloys; Machinery and Machine Elements; Characterization and Analytical Technique